Comprehensive synthesis and characterization of a novel Fe–porphyrin complex: crystal structure, spectroscopic investigations, Hirshfeld surface analysis, and computational modeling (DFT, QTAIM-NCI/ELF) - Dhifet, Mondher; Guelmami, Lelfia; Zaki, Khadija; Zghab, Imen; Sbai, Abdelouahid; Gassoumi, Bouzid (Frontiers in Chemistry, 2025)
In this work, we prepared the novel (η1-hydrogencarbonato) iron (II) picket-fence porphyrin with the formula [K (2,2,2-crypt)][FeII(TpivPP) (η1-HCO3)] (I) (where TpivPP is the (α,α,α,α-tetrakis (o-pivalamidophenyl) (porphinato) anion and (2,2,2-crypt) is cryptand-2,2,2). Complex I was characterized by UV–VIS and IR spectroscopy and single-crystal X-ray diffraction(XRD). These techniques show that the HCO3− axial ligand is coordinated to the Fe2+ metal ion in a monodentate mode. Complex I crystallizes in the P21/n space group with one ion complex [FeII(TpivPP) (HCO3)]- and one counterion [K (2,2,2-crypt)]+. The average equatorial iron–pyrrole nitrogen [Fe–Np = 2.079 (3) Å] bond length and the distance between the iron atom and the 24-atom core of the porphyrin ring [Fe–PC = 0.466 (1) Å] are comparable to those of other five-coordinate, high-spin (S = 2) iron (II) porphyrinates. This is probably due to the electronic repulsion between the dx2-y2 and dxy orbitals and the negative charge of the pyrrole nitrogen. To complement these structural insights, density functional theory (DFT) calculations were performed on the individual ionic components to elucidate their intrinsic electronic properties and reactivity. The molecular electrostatic potential (ESP) maps clearly demonstrated the expected charge complementarity, with a globally positive surface for the [K (2,2,2-crypt)]+ counterion and a predominantly negative potential—localized notably on the oxygen atoms of the η1-hydrogencarbonato ligand—for the [FeII(TpivPP) (HCO3)]− ion complex. Analysis of the frontier molecular orbitals further revealed the electron-donating propensity of the porphyrin π-system and the axial ligand in the anion, juxtaposed with the electron-accepting capability of the cation. Finally, Hirshfeld surface analysis provided detailed insights into the intermolecular interactions within the crystal lattice, highlighting significant non-covalent contacts, including various hydrogen bonds, which govern molecular packing and contribute to the overall crystal stability. This combined experimental and computational approach offers a comprehensive understanding of the structural, electronic, and intermolecular features of this novel iron (II)–porphyrin complex.